If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + t = 2(2x + -1x) + 6 Reorder the terms: t + x = 2(2x + -1x) + 6 Combine like terms: 2x + -1x = 1x t + x = 2(1x) + 6 Remove parenthesis around (1x) t + x = 2 * 1x + 6 Multiply 2 * 1 t + x = 2x + 6 Reorder the terms: t + x = 6 + 2x Solving t + x = 6 + 2x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1x' to each side of the equation. t + x + -1x = 6 + 2x + -1x Combine like terms: x + -1x = 0 t + 0 = 6 + 2x + -1x t = 6 + 2x + -1x Combine like terms: 2x + -1x = 1x t = 6 + 1x Simplifying t = 6 + 1x
| 2/3-2/5-5/6 | | -2a+b=10 | | (D^2+D-6)y=0 | | 1/2x24=y | | x+8-x+3= | | y-5/8=-6(x-3) | | 8+3+x+x= | | 7x-9=-6[x+1]-16 | | M(3)=5x-2 | | y^2+30=64+8x | | X+8+x+3= | | (3x+2y)=51 | | 6(x+2)=6(x+2) | | 8x-25=-1 | | 7y-1=4y+2 | | c-1.8=1.34 | | 4x-2=6-2x | | 2(x-5)=x+5 | | 3x-2x=90+10 | | g(x)=10x-70 | | -18=-9b | | (x^2-5x-14)(4x+28)=0 | | R=2t^2-87t+90 | | 4x-1=5+6[x-3] | | 9.42=3w | | 7[x-5]=4[x-14] | | 24=m+9.7 | | 7[x-8]+5=5x-25 | | (2x+y)=31.75 | | 9[y+3]+3=2y+23 | | 8[x-6]+4=4x-8 | | -3.4=a+1.5 |